1961
DOI: 10.1071/ar9610513
|View full text |Cite
|
Sign up to set email alerts
|

Observations on hair growth and shedding in cattle

Abstract: On three occasions during the period l91S-1956 field observations were made on coat shedding in B. indicus, B. taurus, and B. indicus x B. taurus cattle, and hair and skin samples taken. Measurements of hair length, diameter, and weight per unit area of skin were made, and stages of hair growth within the follicle observed. On two occasions hair data included measurements of length and diameter on individual hairs. Two shedding periods were observed. in spring and in autumn. Approximately 4 months was required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1965
1965
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Exposure of animals from birth to a constant equatorial daylength prevented the normal seasonal shedding response (Yeates, 1957), which suggests the absence of an inherent cycle of pelage changes in cattle. Hayman & Nay (1961) suggest that the pituitary may also be responsive to decreasing day-length, in view of the occurrence of an autumn shedding. On the other hand, Johnson & Ragsdale (1960), McDowell et al (1960) and others have observed marked effects of temperature on coat changes under constant conditions of daylength.…”
mentioning
confidence: 94%
“…Exposure of animals from birth to a constant equatorial daylength prevented the normal seasonal shedding response (Yeates, 1957), which suggests the absence of an inherent cycle of pelage changes in cattle. Hayman & Nay (1961) suggest that the pituitary may also be responsive to decreasing day-length, in view of the occurrence of an autumn shedding. On the other hand, Johnson & Ragsdale (1960), McDowell et al (1960) and others have observed marked effects of temperature on coat changes under constant conditions of daylength.…”
mentioning
confidence: 94%
“…These findings are not substantiated by the present experiments in which full-sized sweat glands were observed associated with hair follicles in all stages of the hair cycle in all instances where the gland was complete and undamaged by cutting and processing. Schleger's claim is surprising because about 60% of the hair follicles in cattle are in the resting phase during the summer (Dowling and Nay 1960;Hayman and Nay 1961) and it would follow that the capacity of cattle to sweat at the warmest time of the year would be drastically reduced.…”
Section: (F) Season and Exercisementioning
confidence: 94%
“…Nay and Hayman (1963) confirmed that sweat gland volume can change with season, but noted that sweat gland shape does not alter with season. Hayman and Nay (1961) and Berman and Volcani (1961) concluded that hair fibre diameter can be larger in summer than in winter in tropical cattle although the former authors failed to find a difference in this parameter in European cattle. Hair length also varies with season.…”
Section: (F) Season and Exercisementioning
confidence: 98%
See 1 more Smart Citation
“…In regard to seasonal differences in sweating capacity, Dowling and Nay (1960) and Hayman and Nay (1961) showed that the winter coat contains a higher proportion of club hairs, representing catagen and telogen phases, than the summer coat. The high proportion of club hairs in winter would mean a high proportion of glands in proximity to the regressed catagen a and telogen phases and this would cause a reduced sweating capacity, such as has been observed.…”
Section: Discussionmentioning
confidence: 99%